Masquerade: an unusual presentation of gall bladder perforation as umbilical fistula. Issue 7 (20th July 2021) - Victor, Naveen Sundaram; Paul, Negine; Munjurpattu, Aparna Jagannathan; Raju, Ravish Sanghi
Abstract : A 75-year-old woman presented with intermittent abdominal pain and distention for 2 months, followed by purulent discharge from the umbilicus for ten days. She was evaluated and diagnosed to have perforation of the gall bladder leading to formation of an anterior abdominal wall abscess which presented as an umbilical fistula. She underwent laparoscopic cholecystectomy along with lay open of abscess in the falciform ligament and curettage of the umbilical fistula tract. She had an uneventful postoperative recovery.